Kajian Pemanfaatan Pemanenan Air Hujan Pada Fly Over Sebagai Alternatif Sumber Air Pertamanan Kota Menggunakan Pendekatan Konsep Eco-Drainase (Studi Kasus:Fly Over Simpang Jalan Jenderal Sudirman - Tuanku Tambusai Kota Pekanbaru) - Geo Gifaj Ruci Adzano; Imam Suprayogi; Muhammad Reza (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
The average value of the free aquifers in Pekanbaru City continues to increase that marked increase in subsidence of groundwater impacted difficulty gaining ground water. Sourced from the Department of Public Works and Spatial Planning Pekanbaru city that watering park in Pekanbaru city used reservoir water from well located in Pekanbaru City Forest, Diponegoro Street, Sail District, Pekanbaru. The water is standard water for the provision of clean water. Therefore, it is necessary to find an alternative water source that can be used for watering City Park. One of them is rainwater. All this time, rainwater only allowed wasted and underused. Though rain water can be used for watering plants. Rain water can be use by rainwater harvesting technology. In this study conducted a study on the utilization of rainwater harvesting at the Fly Over Bridge at intersection of Jenderal Sudirman Street and Tuanku Tambusai Street Pekanbaru City as an alternative water source for City Park. To find the rainwater harvesting donation. Analysis Supported by the software of RainCycle Standard v2.0 program. The large contribution of rainwater harvesting produced is 19% of 120 m3 or 22.8 m3 everyday if not raining and at least 7.7% of 120 m3 or 9.24 m3 everyday if not raining. Keywords: Raincycle Water Harvesting, Fly Over, Alternative Water Resource